A Review on Alzheimer’s Disease: Epidemiology, Etiology, Diagnosis, Management Strategies and Treatment Modalities - Priyanka Tanwar; Mamta Naagar; Manish Kumar Maity (Asian Journal of Pharmaceutical Research and Development, 2024)
One of the most debilitating brain ailments that affect older people is Alzheimer’s disease. It is a condition that is underdiagnosed, undertreated, and rapidly becoming into a significant public health issue. Over the past ten years, there has been a consistent increase in the amount of work done to identify the disease’s etiology and create pharmacological treatments. Improved clinical diagnostic standards and better behavioural and cognitive disturbance treatments are recent breakthroughs. Randomised, double-blind, placebo-controlled, parallel-group studies assessing performance-based assessments of cognitive function, activities of daily living, and behaviour have clinically assessed symptomatic treatment, mostly focussing on cholinergic therapy. Galantamine, donepezil, tacrine, rivastigmine, and other cholinesterase inhibitors are among the medications that are advised for treating cognitive impairment in Alzheimer’s patients. It is debatable and requires further research to determine the function of antioxidants, anti-inflammatory drugs, and oestrogen replacement. Behavioural disturbances are treated with antidepressants, antipsychotics, mood stabilisers, anxiolytics, and hypnotics. The development of new classes of medications that target different neurotransmitter systems (cholinergic, glutamatergic, etc.) for the treatment of behavioural disturbances and cognitive deficits, as well as the development of preventive measures like amyloid p-peptide immunisations and inhibitors of β-secretase and γ-secretase, are some of the future directions in research and treatment of patients with Alzheimer’s disease.